#### Answer

$(x+3)(x+2)$

#### Work Step by Step

RECALL:
A quadratic trinomial $x^2+bx+c$ (with a leading coefficient of 1) can be factored as a product of two binomials if $c$ has factors $d$ and $e$ whose sum is equal to the coefficient of the middle term ($b$).
The factored form of the trinomial is $(x+d)(x+e)$.
Example:
$x^2+3x+2$ can be factored as a product of two binomials since $2=2(1)$ and $2+1=3$, the middle term's coefficient.
The given trinomial has a leading coefficient of 1 and has $c=6$.
Note that $6=3(2)$ and $3+2=5$, the middle term's coefficient.
Thus, the factored form of the trinomial is
$(x+3)(x+2)$.